IMPROVING STUDENT’S WRITING SKILL OF PROCEDURE TEXT THROUGH LOTUS DIAGRAM TO THE ELEVENTH GRADE STUDENT AT SMK SARASWATI 3 TABANAN - NI PUTU AYU KARTIKA SARI DEWI; NI MADE SUPRIYANTI; GUSTI AYU GEDE SUKRANINGSIH; NI KADEK AYU KARTIKA SEPTIANA (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2025)
This study investigates the Lotus Diagram Mapping technique to improve students' writing skills in procedure texts at SMK Saraswati 3 Tabanan. Using a classroom action research (CAR) design, pre-tests and post-tests showed significant improvement, with average scores increasing from 60 to 85. The technique enhanced students' organization, coherence, and clarity while boosting motivation and confidence. The findings highlight the Lotus Diagram as an effective tool for teaching writing in vocational education, with potential for broader application in other contexts and text types.